Incidence of Hepatitis B among Malarial Patients in Islamabad - Dilshad, Fariha; Irfan, Muhammad; Qayyum, Mazhar; Shabbir, Asghar; Ashraf, Asfa; Iqbal, Azara; Iqbal, Muhammad Naeem; Muhammad, Ali (PSM Biological Research, 2016)
The chronic nature of hepatitis B infection influences the clinical approach and management of this disease. The current study was conducted to determine prevalence of hepatitis B among malarial patients in Islamabad. A total of 50 malarial patients were studied by HBsAg assay. Higher prevalence of HBV was found in the 46-60 years age group for both males and females. Among male patients, rate of infection was 25% while in females rate was 23%. The lowest infection rate was recorded in malarial patients older than 60 years. Overall, ratio of infection in males was higher than females. Expected reason of higher infection rate in this age group 46-60 years is the weakness of immune system to fight the environmental as well as pathogenic conditions. Other causes may include the hygienic conditions and residential area responsible for developing malaria. The residential area and hygienic conditions are the necessary components for the health of the residents. Heredity components are also considered in this case. The increasing rate of the disease may decrease with awareness about the disease, its early diagnosis, importance of personal and environmental hygiene and proper maternal checkup.